1999
DOI: 10.47381/aijre.v9i2.438
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Country Voices: Preparing Attracting and Retaining Teachers for Rural and Remote Areas

Abstract: In recent years there has been concern about the equitable provision of education services across metropolitan and rural areas in Australia (Lunn 1997). In particular, much of the debate has revolved around the allocation and distribution of educational and community based resources and the extent to which they hnpact on the lives of teachers living aud working in geographicaliy isolated in areas. Recent political and social debate has highlighted a perceived disenfranchisement and marginalisation of rural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The Australian Human Rights and Equal Opportunity Commission's (HREOC, 2000) national inquiry into rural and remote education concluded that there is a crisis facing rural schools in terms of attracting new teachers. This crisis relates to the preparation, recruitment and retention of rural teachers, particularly in the areas of science, mathematics, and special education teaching (Appleton, 1998;Herrington & Herrington, 2001;White, 2006;Yarrow, Herschell & Millwater, 1999). Similar situations have been identified in the United States (Bolich, 2001;Brewster & Railsback, 2001) and New Zealand (Lang, 1999).…”
Section: Introductionmentioning
confidence: 90%
“…The Australian Human Rights and Equal Opportunity Commission's (HREOC, 2000) national inquiry into rural and remote education concluded that there is a crisis facing rural schools in terms of attracting new teachers. This crisis relates to the preparation, recruitment and retention of rural teachers, particularly in the areas of science, mathematics, and special education teaching (Appleton, 1998;Herrington & Herrington, 2001;White, 2006;Yarrow, Herschell & Millwater, 1999). Similar situations have been identified in the United States (Bolich, 2001;Brewster & Railsback, 2001) and New Zealand (Lang, 1999).…”
Section: Introductionmentioning
confidence: 90%
“…Rural schools in less developed areas of China confront a severe teacher shortage. Rural teachers face several challenges, including low pay, inadequate social support, limited professional development, a lack of incentive mechanisms, a higher number of problem students, complex class management, low social status, poor living conditions, potential cultural conflicts, and so on [4,5]. According to a survey of 5554 instructors in China's Wuling Mountains Zone, the supply of teachers in rural schools is also limited by geography, emotion, and institution [6].…”
Section: Research On Teacher Shortages In Underserved Areasmentioning
confidence: 99%
“…For example, pre-service teacher education programs should provide theoretical and practical components that equip early career teachers to teach multi-age classes (Baills et al, 2002) and Indigenous students (Halsey, 2005;Lock, 2008) competently and with confidence. Addressing these challenges at a systemic level should improve the quality of education that teachers provide to students in remote schools (Yarrow et al, 1999).…”
Section: Unique Environment: "It's Totally Different To Anything That...mentioning
confidence: 99%
“…Having previously lived in a rural location, it can be said that Meg possessed 'social capital' and a 'sense of rural social space' , which assisted her to reside and work in a remote location (Baills et al, 2002;Lock et al, 2009;White & Reid, 2008). Furthermore, Meg demonstrated agency by drawing on this capital and being proactive in developing relationships with the local community (Sharplin, 2002;Yarrow et al, 1999).…”
Section: Relationships: "My Mum's Pretty Good To Talk To"mentioning
confidence: 99%
See 1 more Smart Citation